Metodos de colheita de sementes em (Stylosanthes capitata vog. in Linnaea) - Carmona, R; Ferguson, John E.; Souza Maia, M. de (1986)
Several seed harvesting methods were tested in S. capitata, cv. CIAT-1693 on yield, seed quality and economical data, in Carimágua, Colombia, in 1983. The treatment groups were: A - complete manual, B - Complete mechanical, C -Manual cut and mechanical threshing, D - Mechanical cut and manual threshing. There was variations on treatment A and it was also tested the effect of rethreshing on treatments A, B and C. The experiment was laid out in a completely randomized block design with 3 replications. The harvesting plots consisted of 450m 2 . The mean time spent for harvesting were registered. The combine harvesting have the higher yield of viable seeds, however there was no difference among other treatments. The manual or mechanical rethreshing provided an increase of 10% on final yield. The seeds from rethreshing had lower seed weight, however the viability remained the same. The direct combining resulted in partial scarification of the seeds and the viability of them were reduced. The more profitable treatment was combine harvesting and manual rethreshing after 5 days.